Self-Service Technology (SST) Service Quality, Digitalization, and Customer Satisfaction: Evidence from Bank BRI Special Branch Office - Nathalie Rahmawati; Sri Nawangsari (Pusat Riset dan Inovasi Nasional, 2026)
This study investigates the effect of Self-Service Technology (SST) service quality, including ATM service quality, mobile banking service quality, and Digital Customer Service quality, on customer satisfaction, with digitalization as an intervening variable. The research aims to analyze the varying impacts of different SST channels on customer satisfaction in the context of digital banking. A quantitative approach was employed using primary data collected from 100 customers of Bank BRI Special Branch Office through an online questionnaire and analyzed using SmartPLS 4.0. The results indicate that ATM service quality and Digital Customer Service quality have significant positive effects on customer satisfaction, while mobile banking service quality does not show a significant direct effect. Mobile banking service quality significantly influences digitalization, whereas ATM and Digital Customer Service quality do not. Furthermore, digitalization does not significantly affect customer satisfaction and does not mediate the relationship between SST service quality and customer satisfaction. The model demonstrates strong predictive power, indicating that customer satisfaction is more influenced by direct service quality than by digitalization. These findings provide important implications for banking institutions in optimizing SST service strategies.